Routledge handbook of political Islam - Akbarzadeh, Shahram (Oxon Routledge, 2012)
"This updated, 2nd edition of the Handbook book covers a range of political actors that use Islam to advance their cause. While they share the ultimate vision of establishing a political system governed by Islam, the tactics and methods can be very different. Capturing this diversity, this volume also sheds light on some of the less-known experiences from South East Asia to North Africa. Drawing on the expertise from some of the top scholars in the world, the chapters examine the main issues surrounding political Islam across the world, including: Theoretical foundations of political Islam, Historical background, Geographical spread of Islamist movements, Political strategies adopted by Islamist groups, Terrorism, Attitudes towards democracy, Relations between Muslims and the West in the international sphere, Challenges of integration, Gender relations Capturing the geographical spread of Islamism and the many manifestations of this political phenomenon make this book a key resource for students and researchers interested in political Islam, Muslim affairs and the Middle East"--
Includes bibliographical references and index.
Keywords: Islam and politics; Islam and world politics; Islamic countries -- Politics and government -- 21st century; Islamic countries -- Politics and government -- 20th century